Transcriptome Analysis of the Clostridioides difficile Response to Different Doses of Bifidobacterium breve - Yang, Jingpeng; Yang, Hong (Frontiers in Microbiology, 2020)
Probiotics are widely used in the prevention of Clostridioides difficile infection (CDI). The precise dosage of probiotics is a challenge. In this study, Clostridioides difficile ATCC 9689 (CD) was exposed to different doses of Bifidobacterium breve (YH68). A transcriptomic analysis was performed on CD cells that were separately exposed to low or high doses of YH68 cell-free culture supernatant (CFCS) (CDL or CDH, respectively). The results showed that the inhibitory effect of YH68 (cell pellets or CFCS) on the growth and the damage to the cell membrane integrity of CD exhibited a dose-response relationship at the physiological level. At the transcriptional level, a large number of differentially expressed genes (DEGs) were concentrated in amino acid, carbohydrate, energy metabolism and membrane transport in CDL and CDH cells, suggesting that both doses of YH68-CFCS triggered a significant change in activities in these metabolic pathways. Importantly, a significant stimulation or suppression was found in the pathogenic pathways (quorum sensing, signal transduction, flagellar assembly, biofilm formation and drug resistance) of CDL and CDH cells, whereas there were some differences between the two doses. For example, the expression levels of genes related to quorum sensing and signal transduction in CDH cells were suppressed significantly, whereas genes encoding toxin production and sporulation factors were enhanced; in CDL cells, the expression levels of genes associated with flagellar assembly and biofilm formation were suppressed, whereas genes associated with drug resistance were upregulated significantly. These results indicated that the inhibitory effect of YH68-CFCS against CD, especially in pathogenic and metabolic aspects, did not demonstrate a dose-response relationship at the transcriptional level.